Administrative process in the modern domestic legal doctrine - Гончарук, Степан Тихонович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article deals with main idea and content of administrative process in modern native legal doctrine. Mush attention is paid to the necessity of administrative process understanding in two directions: administration (public administration sphere) and judicial procedure (administrative proceeding).